Linguistic Formality and Audience Engagement: Investors' Reactions to Characteristics of Social Media Disclosures* - Rennekamp, Kristina M.; Witz, Patrick D. (Contemporary Accounting Research, 2021)
ABSTRACT As firms increasingly use social media to provide disclosures to investors, it is important to understand whether the characteristics that are associated with these disclosures lead to different reactions from investors than disclosures provided via more traditional channels. In this paper, we use an experiment to examine whether linguistic formality in positive news disclosures, and engagement of social media users surrounding the disclosures (e.g., “likes” and “retweets”), affect investors' judgments about a firm and its management. Results suggest that, as predicted, investors are more sensitive to signals of audience engagement when disclosures use informal rather than formal language. Specifically, when associated with signals of high audience engagement, the use of informal language leads to greater willingness to invest than the use of formal language in a disclosure. However, also as predicted, the use of informal language hurts willingness to invest when associated with signals of low audience engagement. In two follow‐up experiments, we investigate how news valence and linguistic formality are expected to affect the level of audience engagement in the first place, and we investigate whether managers strategically vary their use of linguistic formality based on characteristics of the setting. Overall, our results provide evidence on how firms might use social media disclosures to better connect with investors. This study contributes to the growing literature on linguistic attributes of disclosures, and the emerging literature investigating the consequences of issuing financial disclosures through social media.